2018
DOI: 10.1186/s13662-018-1851-0
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization for two-dimensional delta operator systems with time-varying delays and actuator saturation

Abstract: In this paper, stabilization is studied for a two-dimensional delta operator system with time-varying delays and actuator saturation. Both lower and upper bounds of the time-varying delays are considered. An estimate of the domain of attraction for the two-dimensional delta operator system is introduced to analyze stability of the closed-loop system. A state feedback controller is designed via a Lyapunov-Krasovskii functional approach for the two-dimensional delta operator system with time-varying delays and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Many scholars have indicated that actuator saturation becomes a serious nonlinearity in control devices. The appearance of actuator saturation in industrial processes will introduce a lower efficiency, bias harmful fluctuations on the output signals along with unwanted responses, or could even result in system failure as well as unstable processes [15][16][17][18]. Hence, a special attention should be paid to the effects of such nonlinearities in the procedure of synthesis, design, and application of fractional-order processes.…”
Section: Introductionmentioning
confidence: 99%
“…Many scholars have indicated that actuator saturation becomes a serious nonlinearity in control devices. The appearance of actuator saturation in industrial processes will introduce a lower efficiency, bias harmful fluctuations on the output signals along with unwanted responses, or could even result in system failure as well as unstable processes [15][16][17][18]. Hence, a special attention should be paid to the effects of such nonlinearities in the procedure of synthesis, design, and application of fractional-order processes.…”
Section: Introductionmentioning
confidence: 99%